Huntingtin exon 1 deletion does not alter the subcellular distribution of huntingtin and gene transcription in mice - Zhao, Xianxian; Sun, Yize; Wang, Zhifu; Chen, Laiqiang; Li, Shihua; Li, Xiao-Jiang (Frontiers in Cellular Neuroscience, 2022)
Huntington disease (HD) is caused by the expansion of CAG triplet repeats in exon 1 of the huntingtin (HTT) gene, which also encodes the first 17 amino acids (N-17) that can modulate the toxicity of the expanded polyQ repeat. N-17 are conserved in a wide range of species and are found to influence the subcellular distribution of mutant Htt. Moreover, N-17 is subject to many posttranslational modifications that may regulate the function, stability, and distribution of HTT. However, the function of Htt exon 1 and its influence on the normal Htt remains to be fully investigated. By investigating a knock-in mouse model that lacks Htt exon1, we found that deletion of Htt exon1 does not affect the survival of mice and differentiation of cultured mouse neurons. Furthermore, the lack of Htt exon 1 does not alter the subcellular distribution of Htt, autophagy protein expression, and global gene transcription in the mouse brain. These results suggest that removing the entire exon 1 of Htt could be a therapeutic approach to eliminate expanded polyQ toxicity.